The Relationship Between Science Process Skills and Students' Creative Thinking Skills on Magnetism in Junior High School - Darmaji; Astalini; Dwi Agus Kurniawan; Bob Widodi (Universitas Pendidikan Ganesha, 2022)
Physics lessons are classified as difficult subjects, so students need to do practical work to make it easier for them to understand the material concept. This study aims to analyze the relationship between students' science process skills and junior high school students creative thinking skills in magnetism. The method used in this study is mixed. This study used a sample of 40 people from class VIII SMP. The sampling technique is Simple Random Sampling. The research instruments used in this study were observation sheets, questionnaires, and interview sheets. The data analysis technique used is quantitative and qualitative data analysis techniques. Quantitative data analysis was carried out using descriptive statistical tests and inferential statistics. This research results show that the percentage of students' science process skills in class VIII C is 70% in the good category. While in class VIII F 75% are in a Good category. Moreover, the percentage of students' creative thinking skills in class VIII C is 60% in the good category, while in class VIII F is 55.0% in the good category. This study concludes that there is a significant relationship between students' science process skills and students' creative thinking skills in class VIII SMP magnetism material. This research implies that it is helpful for teachers and prospective teachers to improve students' science processes and creative thinking skills. Moreover, this research can be used by teachers as a guide to evaluating students' science process skills and creative thinking abilities.